Synthesis of Sacubitril Isomers Governed by Differential Facial Selectivity during the Hydrogenation of Conjugated System - Kurella, Sreenivasulu; Mamidipalli, Phani; Alla, Sampath; Kumari, Neha; Reddy V, Prabhakar; Sharon, Ashoke; Achanta, Srinivas; Bandichhor, Rakeshwar (Synlett, 2025)
A stereoselective process for the synthesis of sacubitril isomers with high yield is reported. Previously reported preparation of these isomers is cumbersome, requiring isolation by repetitive fractional crystallization from the mother liquors remaining after the separation of the major diastereomers (sacubitril) and its enantiomer, respectively. The key feature in our approach is a reversal of stereoselectivity during the catalytic hydrogenation of β,γ-ene amino acid by altering the protecting group on nitrogen. This led to the formation of isomers as the major products providing rapid access to multigram quantities of sacubitril isomers.
Keywords: sacubitril isomers; impurities synthesis; facial selectivity; transition state; spectral analysis